Acquisition of english language prepositions in the absence of formal grammar teaching - Sudhakaran, Beena (Sciedu Press, 2015)
An oft-debated issue is whether or not English grammar has to be taught formally. One group insists that students will not be able to learn grammar unless they are taught formal grammar rules, while the other maintains that students will pick up grammar on their own in due course.